DESAIN NON-PLAYER CHARACTER PERMAINAN TIC-TAC-TOE DENGAN ALGORITMA MINIMAX - Gunadi Emanuel; R. Kristoforus J. Bendi; Arieffianto Arieffianto (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Abstract : Tic-Tac-Toe is one of the board games. It is played by filling the columns on the board with X or O in such a way as to form parallel lines vertically, horizontally and diagonally. This study aims to design Non-Player Characters (NPC) in the tic-tac-toe game with the minimax algorithm. The Tic-tac-toe game will be designed with two game modes: easy and minimum random modes. While in minimax NPC mode will determine the best step. The game development process of the tic-tac-toe application is based on a linear sequence process model. In the analysis phase, the NPC will be designed based on the concept of minimax. Software modeling was designed using Unified Modeling Language (UML), and coded with Visual Basic programming. Our tests show that NPCs with the Minimax algorithm can work well.